In primary care, is measuring free-thyroxine plus thyroid-stimulating hormone to detect hypopituitarism cost-effective? A cost utility analysis using Markov chain models - Brian Shine; Tim James; Amanda Adler (BMJ Open)
Objective We examined whether it is cost-effective to measure free thyroxine (FT4) in addition to thyrotropin (thyroid-stimulating hormone (TSH)) on all requests for thyroid function tests from primary care on adult patients.Background Hypopituitarism occurs in about 4 people per 100 000 per year. Loss of thyrotropin (TSH) secretion may lead to secondary hypothyroidism with a low TSH and low FT4, and this pattern may help to diagnose hypopituitarism that might otherwise be missed.Design Markov model simulation.Primary outcome measure Incremental cost-effectiveness ratio (ICER), the ratio of cost in pounds to benefit in quality-adjusted life years of this strategy.Results The ICER for this strategy was £71 437. Factors with a large influence on the ICER were the utilities of the treated hypopituitary state, the likelihood of going to the general practitioner (GP) and of the GP recognising a hypopituitary patient. The ICER would be below £20 000 at a cost to the user of an FT4 measurement of £0.61.Conclusion With FT4 measurements at their present cost to the user, routine inclusion of FT4 in a thyroid hormone profile is not cost-effective.